WHITE HEAD CABBAGE SEEDS GROWING FROM ROSETTE PLANTS - A. P. Zvedenyuk; V. I. Kazaku (Овощи России)
The terms of seeding on rosette plants have been found. Affect of the elastic adhesive emulsion on the seeds loosing has been revealed.